THE QUESTION OF CLUSTERS IN LESS DEVELOPED AREAS. EMPIRICAL EVIDENCE FROM ROMANIA'S EASTERN REGIONS - Daniela L. Constantin; Constanta Bodea; Carmen B. Pauna; Zizi Goschin; Mariana Dragusin; Ion Stancu (European Regional Science Association (ERSA), 2010)
Various research studies addressing the specific problems and difficulties in the underdeveloped regions in the transition countries from Central and Eastern Europe have identified possible reactions regarding appropriate economic and social policy measures. Some of them take into consideration the role of cluster initiatives as a response to poor competitiveness, low level of innovation, high levels of unemployment and out-migration of the highly-skilled labour force. Though, the simple presence of clusters in a less developed region does not automatically mean more competitiveness and prosperity. A series of policy measures meant to improve the frame conditions for business firms and overall regional development should accompany clusters formation, as a coherent package including economic, legal, institutional, infrastructure, cultural and socio-political elements. Staring from these overall considerations our paper brings into discussion the capacity of cluster policies to offer viable solutions to the Romania's Eastern regions, lagging behind the Western ones. First, an overall image of the clusters existing in the Eastern part of Romania is provided based on statistical methods, mainly location quotients, Gini and Herfindahl indexes of regional specialisation and industrial concentration and cluster analysis. Second, GIS techniques are employed in order to provide a spotlight on cluster identity, location and borders by means of spatial, thematic data at locality level. Performance indicators are also included, so as to get an image on clusters' contribution to the development of the corresponding local economies as well as the county and region economy. Third, based on these results, the interviews with business environment representatives and policy makers in the envisaged regions point out the clusters with the highest chances of success. Also, the best practices are discussed and connected with successful solutions from other Central and East European countries. They will be differentiated in accordance with the characteristics of the North-East and South-East regions, bearing in mind that, however, South-East region has a higher development level and different profile compared with North-East. The paper is the result of a CERGE-GDN funded project.
Keywords: 330; clusters; traditional industries; less developed regions; cluster policies; Eastern Romania